Drama: Guidelines for Teachers of Students with Moderate General Learning Disabilities - O'Sullivan, Carmel (National Council for Curriculum and Assessment, 2003)
One of the main aims in drama is to enable students to make sense of their world and begin to exercise control over their environment. Drama helps students to become aware of the emotional states of others and helps them to develop their ability to create an impact on situations.
PUBLISHED
Dublin, National Stationery Office
Keywords: Creative Arts Practice; Identities in Transformation; Inclusive Society; Arts in Education; Autistic Spectrum disorders; Emotional-behavioural Problems; Intellectual Disability; Sensory impairment; Specific learning difficulties; Accessibility; Children; Education; Policy; Social participation